Tumor-intrinsic PD-L1 signals regulate cell growth, pathogenesis and autophagy in ovarian cancer and melanoma - Clark, Curtis A. (Cancer Res, 2016)
PD-L1 antibodies produce efficacious clinical responses in diverse human cancers, but the basis for their effects remains unclear, leaving a gap in understanding of how to rationally leverage the therapeutic activity. PD-L1 is widely expressed in tumor cells but its contributions to tumor pathogenicity are incompletely understood. In this study, we evaluated the hypothesis that PD-L1 exerts tumor cell-intrinsic signals that are critical for pathogenesis. Using RNAi methodology, we attenuated PD-L1 in the murine ovarian cell line ID8agg and the melanoma cell line B16 (termed PD-L1lo cells), which express basal PD-L1. We observed that PD-L1lo cells proliferated more weakly than control cells in vitro. As expected, PD-L1lo cells formed tumors in immunocompetent mice relatively more slowly, but unexpectedly, they also formed tumors more slowly in immunodeficient NSG mice. A comparative microarray analysis identified a number of genes involved in autophagy and mTOR signaling that were affected by PD-L1 expression. In support of a functional role, PD-L1 attenuation augmented autophagy and blunted the ability of autophagy inhibitors to limit proliferation in vitro and in vivo in NSG mice. PD-L1 attenuation also elevated mTORC1 activity and augmented the anti-proliferative effects of the mTORC1 inhibitor rapamycin. PD-L1 cells were also relatively deficient in metastasis to the lung and we found that anti-PD-L1 administration could block tumor cell growth and metastasis in NSG mice. This therapeutic effect was observed with B16 cells but not ID8agg cells, illustrating tumor- or tissue-specific effects in the therapeutic setting. Overall, our findings extend understanding of PD-L1 functions, illustrate non-immune effects of anti-PD-L1 immunotherapy and suggest broader uses for PD-L1 as a biomarker for assessing cancer therapeutic responses.